Combination of a dielectric continuum model with inverse gas chromatography for the characterization of solid surfaces - Peukert, Wolfgang; Mehler, Carsten; Thielmann, Frank (Adsorption Science & Technology, 2002)
The use of dielectric continuum model for the characterization of solid surfaces was combined for the first time with inverse gas chromatography. Extension of dielectric continuum models to adsorption from the gaseous phase allowed the distributed surface properties of solid surfaces to be determined. An inverse gas chromatograph was used for the measurement of adsorption equilibria as a quick alternative to time-consuming measurements by gravimetric or volumetric set-ups. Combination of the two techniques allowed the rapid determination of the distributed properties of solid surfaces to be effected and the results were interpreted in a fundamental physical sense. This led to a novel and promising way for the rapid and exact characterization of solid surfaces.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.combin
Keywords: dielectric; gas; chromatography; characterization; solid; surface